Influence of Concrete Compressive Strength on the Arching Behaviour of Reinforced Concrete Beam Assemblages. Issue 8 (August 2015) - Pour, H. Vali; Vessali, N.; Foster, S.J.; Samali, B.
The influence of concrete compressive strength on the loading capacity of purely flexural RC members is minor; however, the beneficial effect of concrete compressive strength on the ultimate loading capacity of axially restrained RC beams can be fairly significant due to development of compressive arch action. Accordingly, in this study, six 2/5 th scale restrained RC beam assemblages with various concrete compressive strength (ranging from 18 MPa to 67 MPa) and two different longitudinal steel bar arrangements are tested to establish the relationship between concrete compressive strength and ultimate loading capacity of restrained RC beam assemblages. In addition, nonlinear finite element (FE) model of the tested RC beam assemblages with different boundary conditions were developed and a good correlation between experimental results and FE predictions was observed. With regard to the results captured by the lab tests and nonlinear FE models, it is concluded that the ultimate loading capacity of axially restrained RC beams has an almost linear relationship with compressive strength of concrete and the slope of this line depends on the translational stiffness of end supports (along the beam axis).